(untitled) (Journal of Gender and Social Issues, 2017)
In studying the vast and varied impact of patriarchy on women the researchers applied egalitarian feminist theory with conflict approach in explaining gender inequalities faced by women and the privileges enjoyed by men in every aspect of life in society. The area of research consisted ofInternational Islamic University Islamabad and National University of Modern Languages. 120 female students were selected through random sampling technique. In order to collect information a self-administered questionnaire was applied as a tool of data collection. The findings of research showed that women though claiming to have rights to make their own decisions related to education, mobility, recreation and marriage but they always take permission from someone close to them. Hence it can be concluded that they are almost always kept in darkness of their true rights and liberty, left just to fanaticize about their empowerment and independence.